Identification and distribution of microplastics in sediments in the mangrove area of Nusawiru Batukaras Pangandaran - Romdoniah, Hikmati Suci; Ismail, Mochamad Rudyansyah; Zallesa, Sheila (Universitas Malikussaleh, 2025)
The purpose of this study was to determine the characteristics, distribution and relationship of sedimentation rate to the size of microplastic microplastics in the mangrove area of ​​Nusawiru Batukaras Pangandaran. The research method used is survey and laboratory analysis, namely sampling of waters, sediments and sediment traps at 3 points. Laboratory analysis carried out by the Conservation, Biogeochemistry and Microbiology Laboratory, Building 3, FPIK, Padjadjaran University. The forms found were fiber, film fragments and pellets. The colors found include black, transparent, yellow, gray, brown, red, blue, purple and green. The size of the microplastics found in the samples was <20-5000 µm while in the sediment and sediment trap samples it was 20-5000 µm. The average sedimentation volume rate was 0.083542 ml/m2/14 days and 0.025467 ml/m2/31 days, while the average weight sedimentation rate was 0.129741 gr/m2/14 days and 0.0205075 gr/m2/31 days. While the relationship between the sedimentation rate and the size of the microplastic has no correlation and the form of the relationship is positive and negative. Keywords: Microplastics; Sediment; Sediment Trap; Sedimentation Rate; Water